ETHOS KERJA HINDU DALAM ”BHAGAWADGITA” - Wayan Murniti; I Nyoman Suadnyana (Sekolah Tinggi Agama Hindu Mpu Kuturan Singaraja, 2018)
Work etos does not only deal with way of every nation, but it is more that: it deal with ideology even religion the people follow. The basis of ethics of work ethos of easch nation is built on philosophical uniqueness wich is regarded as their way of life. Work is ethos in Hin dusim put strees on comtemplation ini working (karma yoga), so strere exists balance between materialsm and immarialism.